The Impact of Hu’s Music Diplomacy on Mongolia’s Tourism National Branding Program - Muhammad Ihsanusyauqie; Gilang Nur Alam (Publikasi Indonesia, 2024)
This study aims to analyze the impact of Hu's music diplomacy on Mongolia's national branding program. The study employs a descriptive qualitative method with secondary data analysis from journal articles, books, relevant reports, and media covering The Hu's activities. The results indicate that The Hu, with their unique approach of combining traditional Mongolian music elements with modern rock, has successfully raised global awareness of Mongolian culture and enhanced the country's positive image. Their international performances received awards, and collaborations with renowned musicians have introduced Mongolian cultural elements to a wider audience, creating curiosity and appreciation for Mongolia's cultural heritage. Strategic recommendations include greater government support, enhanced collaboration with digital platforms, and educational and cultural exchange programs.